Internet Financial Reporting Pada Rumah Sakit Berstatus Badan Layanan Umum: Perlukah? - Resha Dwi Ayu Pangesti Mulyono; Fahmi Firdaus (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2021)
Based on PP. 74 of 2012 on the change of hospital status to Public Service Board (RS-BLU) changed the perspective of the responsibility of the hospital in informing its operational performance. The practice of preparing and presenting the RS-BLU financial statements in Indonesia is not in accordance with PSAK 45, thus indicating financial management that is not in accordance with the financial accounting standard (SAK) that has been determined and affects stakeholder decision-making related to budget acceptance accessibility due to limited relevance of performance information sources on its financial statements. The purpose of this research is to analyze the increase of financial reporting value stakeholder through presentation of financial statements based on PSAK 45 with internet financial reporting as a detector to build stakeholder trust and increase source of RS-BLU budget revenue. The research method used is descriptive qualitative method describes, describes, compare a data with theory based on literature study that obtained from the source of publication documentation (The Asian Sun Life Index of Health in 2017). The results show that most of the RS-BLU in Indonesia do not apply financial reporting according to PSAK 45 and have a negative image in the eyes of their stakeholders, low capital financing and RS-BLU health service quality decreased by 65%.